Carlo Lorenzini e la pedagogia illuminista - Poettinger, Monika (Studi sulla Formazione/Open Journal of Education, 2018)
This essay analyses several writings of Carlo Lorenzini, published on jour-nals, newspapers and collections, reconstructing the enlightened pedagogical principles applied in composing his masterpiece, The Adventures of Pinoc-chio, and also his assumptions in regard the path of history and the role of education in the bettering of society. The process of humanization of Pinoc-chio will also be represented as the experience of all children, aged eight to twelve, on the verge of adulthood in the land of freedom of choice and moral-ity building. Lastly, the work of Lorenzini will be contextualised in the his-tory of Tuscany in the decades of Italy’s unification, showing the disap-pointment of Lorenzini with the results of the institutionalisation process of the new state, harming the freedom of its citizen, not least by imposing bourgeois values through compulsory education.